Brainstem auditory‐evoked response (BAER) in client‐owned pet ferrets with normal hearing. (7th June 2014) - Piazza, S.; Huynh, M.; Cauzinille, L.
Abstract : The objective of this study was to evaluate the feasibility of brainstem auditory‐evoked response (BAER) testing in pet ferrets in a clinical setting, and to describe a routine method and baseline data for normal hearing ferrets for future investigation of deafness in this species. Twenty‐eight clinically normal client‐owned ferrets were included. BAER measurements were recorded under general anaesthesia (isoflurane delivered by mask), from subcutaneously placed needle electrodes. A 'click' stimulus applied by insert earphone with an intensity of 90 dB sound pressure level (SPL) was used. The final BAER waveform represents an average of 500 successive responses. Morphology of the waveform was studied; amplitude and latency measures were determined and means were calculated. The BAER waveform of the normal ferret included 4 reproducible waves named I, II, III and V, as previously described in dogs and cats. Measurements of latencies are consistent with previous laboratory research using experimental ferrets. In the present study, a reliable routine protocol for clinical evaluation of the hearing function in the pet ferret was established. This procedure can be easily and safely performed in a clinical setting in ferrets as young as eight weeks of age. The prevalence of congenital deafness in ferrets is currently unknown but may be an important consideration, especially in ferrets with a white coat. BAER test is a useful screening for congenital deafness in this species.